EVALUASI PEMANFAATAN KOLEKSI PUSTAKA DI DINAS PERPUSTAKAAN KOTA PONTIANAK - Didi Satriadi; A. Totok Priyadi (Universitas Tanjungpura, 2021)
AbstractThis study aims to evaluate the utilization of collections in the Pontianak CityLibrary Office. The method used is qualitative research method. Intrumenguidelines used in this study are observations, interviews, documentation. Theresults showed that the collection of books that are most often used in thePontianak City Library Office is seen from the circulation data of visitors in2019, namely as many as 15,381 people and books that are most often utilizedby musicians based on the classification number in 2019 the most widelyutilized pemustaka is in the collection of literature with a classification numberof 800 and the lowest art group, entertainment and sports with a classificationnumber of 700 and the obstacles faced by the library in utilizing the collection,namely the collection of library materials is still lacking complete andconfusion in the utilization of the collection.Keywords: Utilization of Collections, Library Materials, Pontianak City Library